Potensi Minyak Atsiri Temu Kunci (Kaempferia pandurata) dan Komponennya sebagai Pelangsing Aromaterapi - Irma Hermawati Suparto; Rahmi Nur Wahidah; Irmanida Batubara (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Temu kunci (Kaempferia pandurata) is one of the Indonesian aromatic plants containing essential oils. The objective of this study was to evaluate the potential compound in temu kunci essential oils that has activities as slimming aromatherapy. Essential oil was obtained from the rhizome by distillation then further fractionated using column chromatography and obtained 7 fractions. Based on the gas chromatography mass spectrometer, the main component of the essential oil of temu kunci was o-cymene, while the main component in fraction 1 was limonene. Fraction 1, camphor and the essential oils were tested in vivo as slimming aromatherapy using adult male Sprague Dawley rats given for 5 weeks. Animals received inhalation of camphor and essential oils showed a higher tendency to increase body weight compared to animals given fraction 1. Animals treated with fraction 1 showed the lowest body weight gain response (47%) eventhough not significant, however it gave the lowest total consumption per weekly (P<0.05). Therefore, based on these results, fraction 1 that has limonene is potential as slimming aromatherapy agent.